Development of nutraceutical formulations based on the mycelium of Pleurotus ostreatus and Agaricus bisporus. Issue 6 (23rd May 2017) - Cardoso, Rossana V. C.; Fernandes, Ângela; Oliveira, M. Beatriz P. P.; Calhelha, Ricardo C.; Barros, Lillian; Martins, Anabela; Ferreira, Isabel C. F. R.
Abstract : Agaricus bisporus and Pleurotus ostreatus mycelium were explored with the aim to be used in the development of new nutraceutical formulations, highlighting the potential of in vitro culture as a tool to improve phenolic acids and ergosterol production. Abstract : The present work is aimed at developing nutraceutical formulations based on the mycelium of Agaricus bisporus and Pleurotus ostreatus, highlighting the potential of in vitro culture as a tool to improve the production of bioactive compounds, namely phenolic acids and ergosterol. The mycelia of both species were cultured in different solid and liquid media in order to compare the growth rate and yielded biomass. Fruiting bodies, mycelia and culture media were compared regarding the antioxidant activity, anti-inflammatory effects in RAW264.7 cells and cytotoxicity in human tumor cell lines and non-tumor porcine liver cells. P. ostreatus mycelia showed higher contents of ergosterol and phenolic compounds, and stronger antioxidant activity than the corresponding fruiting body. P. ostreatus and A. bisporus did not show anti-inflammatory activity, and P. ostreatus was the only one showing cytotoxicity in tumor cell lines. The results show that these mushrooms provide compounds with antioxidant and cytotoxic capacities, with variations among species.